(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The "onion aphid", Neotoxopteraformosana (Takahashi), is recorded for the first time in Italy, where it is infesting chives (Allium schoenoprasum) in the area of Oppeano (Verona). So far, the aphid was well known for Eastern Asia, the Arnericas and Australasia; also recorded in Europe from Finland, where it was detected on imported onion sets a few years ago. Short biological and epidemiological notes are given, in addition to a few morphological details, in arder to separate this species from the quite relative ones, N. oliveri (Essig) and N. violae (Pergande).